Design and Angle of Contact (AoA) analysis of Remote Control (RC) Aircraft (International Journal of Innovative Research in Engineering & Management, 2022)
In this paper, the design of a prototype of  Remote Control (RC) aircraft is discussed. It is important  and interesting to learn about the workings, terminology,  factors affecting to flight, construction, application, and  advantage of the aircraft. Also, studied about the  designing aeronautics formula rules and analytical  equations of aircraft lift force and drag force of a RC  airplane for AOA analysis. In addition, aerodynamic  performance is carried out on the airfoil type wing to  determine the drag and lift forces at maximum speed.
Keywords: RC Airplane; Design; 3D Modeling; AOA; Drag Force; Lift Force; Analytical formulas